Pelatihan Fotografi Produk Dengan Menggunakan Mini Box Studio Pada Ukm Walidayna: - Suprianingsih; Dani Manesah; Desipriani Desipriani (JURNAL BESEMAH : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The purpose of carrying out this community service activity, firstly, is to fulfill the tridarma duties of the tertiary institution, secondly, to provide useful training for UKM Walidayna to be able to produce attractive and good product photos, to be able to attract consumer interest. The technique of taking photos using a mini box is very suitable for making product catalogs for SMEs which usually have a limited bag for their marketing field. Mini box is a photo taking technique that uses a mini studio with raw materials that are relatively cheap and easy to obtain with good results and is not inferior to photos produced by large photo studios which usually cost a lot.